Respuesta :

Answer:

( -1/2) ^5

Step-by-step explanation:

We know that a^b* a^c = a^(b+c)

( -1/2) ^ 3 * ( -1/2) ^2

( -1/2) ^ (3+2)

( -1/2) ^5

Answer:

[tex]{\huge{\pink{\underline{\underline{Solution:}}}}}[/tex]

[tex] {( \frac{ - 1}{2}) }^{3} × {( \frac{ - 1}{2}) }^{2} \\

=>{( \frac{ - 1}{2}) }^{(3+2)}\\

=>{( \frac{ - 1}{2}) }^{5}\\

=> \frac{ - 1}{2} \times \frac{ - 1}{2} \times \frac{ - 1}{2} \times \frac{ - 1}{2} \times \frac{ - 1}{2} \\

=> \frac{ - 1}{32} [/tex]

[tex]{\huge{\pink{\underline{\underline{Formula\ used:}}}}}[/tex]

[tex]{a}^{x}×{a}^{y}={a}^{x+y}[/tex]